2019
DOI: 10.1186/s13036-019-0180-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile analysis of long non-coding RNA in skeletal muscle of osteoporosis by microarray and bioinformatics

Abstract: Background Osteoporosis (OP) is a condition featured by bone mass loss and bone tissue microarchitectural alterations due to impaired tissue homeostasis favoring excessive bone resorption versus deposition. The trigger of such an impairment and the downstream molecular pathways involved are yet to be clarified. Long non-coding RNA (lncRNA) plays a role in gene transcription, protein expression and epigenetic regulation; and altered expression results in immune or metabolism related desease develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…The mutation of PNPLA7 gene (rs3812499) is related to rheumatoid arthritis [23]. It is found that SCD is up-regulated in skeletal muscle tissues of patients with osteoporosis [24]. Moreover, high SCD activity significantly increases the risk for fracture in men [25].…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of PNPLA7 gene (rs3812499) is related to rheumatoid arthritis [23]. It is found that SCD is up-regulated in skeletal muscle tissues of patients with osteoporosis [24]. Moreover, high SCD activity significantly increases the risk for fracture in men [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we report the presence of a unique set of lncRNAs in the serum-derived exosomes with significant functional implications in osteoporosis. Although the function of the majority of lncRNAs remains to be elucidated, previous studies have indicated that lncRNAs may be involved in the pathogenesis of osteoporosis (Kung et al, 2013 ; Fei et al, 2018 ; Liu et al, 2019 ). We were also able to validate 11 differentially expressed lncRNAs by quantitative PCR using lncRNA specific primers ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…IncRNAs regulate gene expression by recruiting transcriptional factors, by acting on the RNA polymerase machinery or by sequestrating the microRNA that silence the mRNA expression (Dykes and Emanueli, 2017 ; Silva et al, 2019 ). A study by Liu et al ( 2019 ), reported that about 1,500 lncRNAs were differentially expressed in case of osteoporotic conditions out of which around 250 lncRNAs showed significant variation. Other studies also have indicated the roles of few long non-coding RNAs like lncRNA RP11-498C9, lncRNA XR111050, lncRNA ANCR in regulation of osteogenic gene expression (Li et al, 2019 ; Silva et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Seeliger et al (2014) also identified five freely circulating miRNAs associated with osteoporosis fractures. There is increasing evidence that lncRNAs also play important roles in the pathogenesis of osteoporosis (Peng et al, 2018;Feng et al, 2019;Liu et al, 2019). In this study, we obtained lncRNA profiles of osteoporosis patients by repurposing array probes on publicly available microarray data and performed genome-wide analysis for expression patterns of lncRNAs, miRNAs, and mRNAs between high-and low-BMD subjects.…”
Section: Discussionmentioning
confidence: 99%